Intercropping of Pea and Spring Cereals for Weed Control in an Organic Farming System - Šarūnaitė, Lina; Arlauskienė, Aušra; Maikštėnienė, Irena Deveikytė Stanislava; Kadžiulienė, Žydrė (IntechOpen, 2012)
None